A Novel Semiautomated Fractional Limb Volume Tool for Rapid and Reproducible Fetal Soft Tissue Assessment. (7th June 2016) - Mack, Lauren M.; Kim, Sung Yoon; Lee, Sungmin; Sangi-Haghpeykar, Haleh; Lee, Wesley
Abstract : The purpose of this study was to document the reproducibility and efficiency of a semiautomated image analysis tool that rapidly provides fetal fractional limb volume measurements. Fifty pregnant women underwent 3‐dimensional sonographic examinations for fractional arm and thigh volumes at a mean menstrual age of 31.3 weeks. Manual and semiautomated fractional limb volume measurements were calculated, with the semiautomated measurements calculated by novel software (5D Limb Vol; Samsung Medison, Seoul, Korea). The software applies an image transformation method based on the major axis length, minor axis length, and limb center coordinates. A transformed image is used to perform a global optimization technique for determination of an optimal limb soft tissue boundary. Bland‐Altman analysis defined bias with 95% limits of agreement (LOA) between methods, and timing differences between manual versus automated methods were compared by a paired t test. Bland‐Altman analysis indicated an acceptable bias with 95% LOA between the manual and semiautomated methods: mean arm volume ± SD, 1.7% ± 4.6% (95% LOA, −7.3% to 10.7%); and mean thigh volume, 0.0% ± 3.8% (95% LOA, −7.5% to 7.5%). The computer‐assisted software completed measurements about 5 times faster compared to manual tracings. In conclusion, semiautomated fractional limb volume measurements are significantly faster to calculate when compared to a manual procedure. These results are reproducible and are likely to reduce operator dependency. The addition of computer‐assisted fractional limb volume to standard biometry may improve the precision of estimated fetal weight by adding a soft tissue component to the weight estimation process.